Evaluation of fine needle aspiration biopsy in oral cavity and head and neck region with different stains techniques - Ana Paula Candido dos SANTOS; Norberto Nobuo SUGAYA; Décio dos Santos PINTO Jr.; Celso Augusto LEMOS Jr. (Brazilian Oral Research, 2015)
The present study aimed to evaluate the Fine Needle Aspiration Biopsy in different staining techniques in nodular lesions of the oral cavity and head and neck region, as their sensitivity, specificity and accuracy, staining with Panoptic, Papanicolaou and Hematoxylin-Eosin (H&E) stains. 46 patients who sought the Clinic of the Discipline of Clinical Stomatology at FOUSP were selected consecutively, with nodular lesions in the oral cavity and head and neck region. The material obtained by FNAB was sent on 6 different slides, stained by the method of Panoptic, Papanicolaou and H&E, to the same pathologist only with the clinical diagnosis. After the final report of FNAB, the biopsy report was issued, serving as gold standard. After the calculations, the results of sensitivity, specificity and accuracy for Panoptic staining were 28.6%, 76% and 15.4%, respectively. The result of sensitivity, specificity and accuracy for Papanicolaou staining were 71.4%, 76.7% and 23.3%, respectively. The result of sensitivity, specificity and accuracy for H&E staining were 82.1%, 23.3%, 28.6%, respectively. We can conclude, according to the methodology of this study that, H&E and Papanicolaou stains showed the same sensitivity of diagnosing malignant neoplasms. H&E stain showed a better specificity for diagnosing benign neoplasms, compared with Papanicolaou and Panoptic stains. H&E stain showed better accuracy, to give definitive diagnosis, followed by Papanicolaou and Panoptic stains.